Jute and Luffa Fiber-Reinforced Biocomposites: Effects of Sample Thickness and Fiber/Resin Ratio on Sound Absorption and Transmission Loss Performance - GENÇ, GARİP (TAYLOR & FRANCIS INC, 2021)
The acoustic properties of natural fiber-reinforced composites should be identified before using these materials in various engineering applications including sound and vibration isolation. This study investigates the effects of sample thickness and fiber/resin ratio on the acoustic performance of jute and luffa fiber-reinforced biocomposites. For this purpose, jute and luffa composite samples with different thicknesses and fiber/epoxy ratios are manufactured and their sound absorption coefficients (SACs) and transmission losses (TLs) are determined using impedance tube method. Thickness-dependent tendencies of the SACs and TLs of jute and luffa composites for low-, medium-, and high-frequency ranges are identified. The effect of fiber/epoxy ratio on the acoustic properties of jute and luffa composites as a function of frequency are determined. Furthermore, the SACs and TLs of some natural fiber-based samples with different thicknesses are predicted using mathematical models and the theoretical and experimental results are compared and evaluated.
Keywords: Jute; luffa; biocomposites; fiber/resin ratio; sound absorption; transmission loss